N-type doping and morphology of GaAs nanowires in Aerotaxy. (10th May 2018) - Metaferia, Wondwosen; Sivakumar, Sudhakar; Persson, Axel R; Geijselaers, Irene; Wallenberg, L Reine; Deppert, Knut; Samuelson, Lars; Magnusson, Martin H
Abstract: Controlled doping in semiconductor nanowires modifies their electrical and optical properties, which are important for high efficiency optoelectronic devices. We have grown n -type (Sn) doped GaAs nanowires in Aerotaxy, a new continuous gas phase mass production technique. The morphology of Sn doped nanowires is found to be a strong function of dopant, tetraethyltin to trimethylgallium flow ratio, Au–Ga–Sn alloying, and nanowire growth temperatures. High temperature and high flow ratios result in low morphological quality nanowires and in parasitic growth on the wire base and surface. Alloying and growth temperatures of 400 °C and 530 °C, respectively, resulted in good morphological quality nanowires for a flow ratio of TESn to TMGa up to 2.25 × 10 −3 . The wires are pure zinc-blende for all investigated growth conditions, whereas nanowires grown by metal-organic vapor phase epitaxy with the same growth conditions are usually mainly Wurtzite. The growth rate of the doped wires is found to be dependent more on the TESn flow fraction than on alloying and nanowire growth temperatures. Our photoluminescence measurements, supported by four-point probe resistivity measurements, reveal that the carrier concentration in the doped wires varies only slightly (1–3) × 10 19 cm −3 with TESn flow fraction and both alloying and growth temperatures, indicating that good morphological quality wires with high carrier density can be grown with low TESn flow. Carrier concentrations lower than 10 19 cm −3 can be grown by further reducing the flow fraction of TESn, which may give better morphology wires.